The specialist qualities of implementing an art education curriculum for learners with special needs from the teachers’ standpoint - Vaitkevičienė, Asta; Jokubauskienė, Ona (Special Education, 2016)
The article deals with the qualities required in implementing an art education curriculum for learners with special needs. There are few studies disclosing how teachers approach an art education curriculum with learners who have special educational needs. Therefore, it is relevant to investigate how teachers understand and think about the purpose of art education for learners with special needs, and how they assess such activities provided in the art education curriculum. It is concluded that through implementing an art education curriculum for children with special needs, teachers must understand the purpose of art education and are convinced that the creative activities of learners with special needs stimulate their imagination, develop creativity and enhance self-confidence. During art education activities teachers are ready to take into account pupils’ individual abilities and differentiate tasks. Teachers understand the role of art education in the development of the personality of learners with special needs but controversially? Clarify, why is it controversial? assess the trends of art activities.